Implementasi Pelaksanaan Program Kerja Kampus Mengajar Batch 5 Di SDS NU Kencong - Fatmawati Fatmawati; Astri Widyaruli Anggraeni (LPPM Politeknik Pratama, 2024)
The aim of the Teaching Campus program is to help students carry out the teaching and learning process in local schools. This research uses qualitative methods. The subjects of this research were SDS NU KENCONG, totaling 115 students. Meanwhile, the object of this research is the implementation of the teaching campus at SDS NU Kencong. Data collection in this research was carried out using observation and documentation techniques. The first program implemented was the literacy work program in the form of fun reading reading corners, reading concentration and PAKARLAKA learning media. The second is a numeracy work program in the form of multiplying cute numbers and there is music and a quiz. The third is the school administration work program in the form of school accreditation, reading corners and library arrangement.